2022
DOI: 10.1021/acsphyschemau.2c00015
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Thermodynamics of the Dimers and Trimers of H2 and D2 and Their Heterodimer (H2)(D2)

Abstract: The equilibrium thermochemical properties of the dimers and trimers of H 2 and D 2 are obtained from the equations of state (EOSs) of normal H 2 and D 2 . The standard dimer and trimer equilibrium constants K D o and K T o and ΔH D, T o and ΔS D, T o are reported for these weakly bound van der Waals molecules between 25 and 45 K. Statistical thermodynamics (ST) calculations of H 2 and D 2 dimerization using Morse pair potentials to account for intermolecular interactions, obtained from recent experimental work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For the rare gas dimers, quasi-bound rotational levels were included in the summations. These calculations, which have been reported before, are applied in the present work to the dimers at the respective 0.7 T c temperatures. The last column of Table contains the results of these calculations.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…For the rare gas dimers, quasi-bound rotational levels were included in the summations. These calculations, which have been reported before, are applied in the present work to the dimers at the respective 0.7 T c temperatures. The last column of Table contains the results of these calculations.…”
Section: Resultsmentioning
confidence: 92%
“…In four recent publications, the equilibrium thermodynamic properties of the dimers and trimers of five rare gases helium to xenon, , as well as H 2 , D 2 , CO 2 , and CH 4 , were reported. In the present work, such calculations are applied to these nine species, as well as to other nonpolar gases, CF 4 , ethane, ethene, SF 6 , propane, and 2,2-dimethylpropane (neopentane).…”
Section: Background and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of studies have been reported concerning the nature of the interactions between the components, few have dealt with the equilibrium thermodynamic properties of van der Waals dimers and trimers. In recent publications, such information has been obtained from the equation of state (EOS) of the rare gases He – Xe and for 10 nonpolar molecules ranging from H 2 to C­(CH 3 ) 4 . Since the thermodynamic properties of heterodimer formation cannot be obtained from the EOS-based method that can be employed for the homodimers, we sought an approach that could be applied to all three dimers, (N 2 )­(N 2 ), (O 2 )­(O 2 ), and (N 2 )­(O 2 ). Such calculations would provide consistency to the results thus obtained.…”
Section: Introductionmentioning
confidence: 99%